Exercise and Falls in Elderly Individuals: an Examination of Graduate Theses Written Between 2000-2025 in Turkiye - SAHIN, Yigit; ERZEYBEK, Mustafa Said (International Journal of Holistic Health, Sports and Recreation, 2025)
This research aims to examine the graduate theses written between 2000-2025 in Turkey, which address exercise and falls in elderly individuals. The main purpose of the research is to analyze and interpret the graduate theses written in this period and develop new suggestions. This research was conducted as a descriptive systematic review using the literature review method. The sample of the study was selected from theses registered in the Higher Education Council National Thesis Center. As a result of the data obtained, the number of theses, subject titles, distribution by years, data collection methods, tools used, sample groups, and topics studied were identified. In the research, the document analysis method was utilized, and a Thesis Classification Form was used to analyze the theses. According to the findings of the research, a total of 5 master's theses, 11 doctoral theses, and 1 specialization thesis were written between 2000-2025, with 1 doctoral thesis being restricted by the author. It was observed that the majority of these theses (63%) belong to the doctoral level, and they are in the fields of nursing, physiotherapy, and rehabilitation. Regarding data collection methods, it was seen that most of the studies (71%) used pre-test post-test and randomized controlled methods. It can be concluded that the number of master's theses with detailed analyses on exercise and falls in elderly individuals should increase, and more mixed methods should be used to provide more meaningful contributions to the field literature.